(untitled) (Damascus University Journal of agriculture sciences, 2025)
In this research, a single-effect vertical diffusive solar still was designed and evaluated with a design productivity of 5 [L/m2] equipped with a flat solar collector. Its performance was evaluated by comparing the amount of measured distilled water with theoretical values calculated in different periods of years 2020-2021, as the results of the theoretical study showed that volume of the single-effect diffuse vertical solar distiller is 0.25 [m3] and area of the flat solar collector is 0.64 [m2]. The highest value for quantity of distilled water was recorded during July, with an average of 4.8 [L/m2], which is equivalent to 96% of the design value. Its average productivity during June and August was 4.2 [L/m2], which is equivalent to 84% of the design value. Pearson correlation coefficient (r) was 0.99 and Nash-Sutcliffe model efficiency coefficient (EF) 0.95, this indicates a great convergence between the amount of water calculated theoretically and the amount of water measured experimentally. Where this indicates that simulating the design theoretical model with the experimental model is of high accuracy, Therefore, the size of the single-effect vertical diffusive solar distiller designed for this research is considered an appropriate means to obtain the amount of water to be obtained.